Propuesta de implementación de nuevo punto de venta de Comisariato de Carnes El Rancho con valor agregado en sector socio económico medio alto – alto. - Decker Lema, Andrés Renato (2019)
In this work, the feasibility of opening a new distribution point to cover a niche market of upper - middle class in the city of Guayaquil was evaluated. In order to evaluate the feasibility of the project a study of the external factors and internal capacities of the company was carried out. In the theoretical framework, theories such as consumer behavior, efficiency indicators of retail distribution, competitiveness and added value in retail companies were considered. The results of the investigation indicate that the company is in an aggressive position, that is to say that it is growing in a mature industry. The results show that the company has the financial capacity to invest in a market with many entry barriers, which allows it to take advantage of its 30-year experience in the market. The recognition of brand and experience, together with the high competition, makes it difficult for new competitors to enter and that gives the “Comisariato de Canes El Rancho” an advantage. Finally, the strategy of vertical forward integration should seek a greater number of strategic alliances with other distributors, while continuing to open direct channels of purchase for large customers such as restaurants and hotels. To conclude the analysis, the feasibility of the project was demonstrated with a very attractive financial valuation of 50% of the Internal Rate of Return and $ 170,912.24 of Net Present Value.